RANCANG BANGUN ELEKTROSTIMULATOR BERBASIS ARDUINO MEGA 2560 - Muslihun, Muslihun; Ulin Nuha ABA, Muhammad; Ringaama Kromen3, Yohanes (MEDIKA TRADA : Jurnal Teknik Elektomedik Polbitrada, 2023)
The use of medical equipment in the world of health is very much needed, one of which is an electrostimulator which can be used to help recovery in post-stroke patients. Electrostimulators can be made with several conditions, namely: controller, stimulator, and electrodes. Apart from that, there are 4 parameters needed for the electrostimulator, namely 1) Pulse Amplitude, 2) Pulse Width, 3) Pulse Shape, 4) Pulse Frequency. In this electrostimulator, it is highly recommended to use a surface electrode, apart from being a non-invasive electrode, this electrode also provides comfort and is easy to use. Judging from this, an innovation was carried out, namely making an electrostimulator with the choice of 2 modes, namely continuous and intermittent. The research procedure was carried out in several stages starting from preparing tools and materials, measurements and functional tests. The results of the research are a design for an electrostimulator therapy device with a power supply connected to a microcontroller and displayed on an LCD. The test results showed that the error percentage at the power supply input was 5.9%, the power supply output was 3%, and the buzzer output was 0%. The results of testing and analysis of the tool on the oscilloscope showed that the error percentage at frequency values of 2 Hz, 4 Hz, 5 Hz, 7 Hz and 8 Hz was 0.05%, 0%, 2%, 4% and 8% respectively. Based on the results of this research, it can be concluded that the tool is as desired and good to use.